The impact of financial constraints on accounting conservatism - Demonier, Gladyson Brommonschenkel; Almeida, José Elias Feres de; Bortolon, Patricia Maria (Review of Business Management, 2015)
Objective – This study investigates the effects of financial constraints on the conservatism practices of Brazilian firms. Design/methodology/approach – A sample totaling 1,086 observations of Brazilian publicly traded companies listed on BM&FBovespa was developed from 2000 to 2012. In the sample 106 observations were classified in condition of financially constrained according to the criteria related to lower dividends payout, large amount of cash and equivalents available and investment or capital expenditures (property, plant and equipment). We use Basu (1997) and Ball and Shivakumar (2005) models to investigate the relationship between financial constraints and accounting conservatism. Findings – The results show financially constrained firms adopt less conditional conservatism practices on their accounting figures. In other words, those firms avoid to disclose losses trying to access more external funds, however, increasing information asymmetry. Practical implications – The evidence of this study could be used by creditors and regulators to support new financing policies and risk monitoring through firms’ financial statements. Originality/value – We empirically show that conditional conservatism practices are affected by financial constraints. Also, we develop an alternative way to classify companies in terms of financial constraints from a combination of three proxies traditionally applied in the literature such as cash and cash-equivalent, capital expenditure (property, plant and equipment) and dividends payout.